SIMULASI SISTEM PEMBAYARAN RETRIBUSI GERBANG PARKIR MENGGUNAKAN MIKROKONTROLER AT89S51 - Suwarno, Pujo; Widodo, Thomas Sri (Jurnal Teknik Elektro, 2009)
In line with development of science and technology, giving many ease to us to do various activities from thing which is easy until complicated thing. Control system increasingly plays important role in assisting human life every day. One of controller system which many enthused is microcontroller. In this scheme of writer will build a system use microcontroller as its controller. Appliance which will be designed is a simulation system payment of retribution gate park to use AT89S51 microcontroller. This Appliance will work when vehicle get through the gate park. Vehicle moment get through the gate park will be detected by sensor to open of enter latch, and close of enter latch. Later, its detected by light sensor at retribution area to determine vehicle type so that display of LCD ( Liquid Crystal Display) puts forward vehicle type information and many coin to be paid. Having taken steps payment of retribution, controller of exit latch will open and close automatically Keyword :ÃÂ  Light Sensor (LDR), AT89S51 Microcontroller, LCD M1632,limmit switch, Motor of DC. ÃÂ